The Effectiveness of Visualization on Cognitive Load and Problem-Solving in Gifted and Non-Gifted Students - Ben-Motreb, Khaled; Al-Makhalid, Khalid (Anales de Psicología / Annals of Psychology, 2026)
This study examined the impact of visualization techniques on mathematical problem-solving performance and cognitive load among 80 male high school students (40 gifted, 40 non-gifted) in Saudi Arabia. Using a pretest-posttest experimental design, participants were randomly assigned to an experimental group (n = 40), receiving visualization-based instruction (e.g., diagrams, interactive tools), or a control group (n = 40), using traditional methods. Data were analyzed with two-way mixed ANOVAs and a MANOVA. Results showed the experimental group significantly outperformed the control group in problem-solving over time, F(1, 76) = 99.45, p < .001, η²ₚ = .57, and experienced reduced cognitive load, F(1, 76) = 47.40, p < .001, η²ₚ = .37. A significant interaction effect emerged (Wilks’ Λ = .88, F(2, 75) = 5.12, p = .008, η² = .12), with gifted experimental students achieving the highest scores (M = 88.45, SD = 4.29) and lowest cognitive load (M = 3.05, SD = 0.61). These findings highlight visualization techniques as effective for enhancing mathematics education, especially for gifted learners, supporting inclusive instructional strategies.